2010
DOI: 10.5194/bgd-7-5119-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcifying invertebrates succeed in a naturally CO<sub>2</sub> enriched coastal habitat but are threatened by high levels of future acidification

Abstract: CO2 emissions are leading to an acidification of the oceans. Predicting marine community vulnerability towards acidification is difficult, as adaptation processes cannot be accounted for in most experimental studies. Naturally CO2 enriched sites thus can serve as valuable proxies for future changes in community structure. Here we describe a natural analogue site in the Western Baltic Sea. Seawater pCO2 in Kiel Fjord is elevated for large parts of the year due to upwellin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 38 publications
(14 reference statements)
4
82
2
Order By: Relevance
“…However, we know that in the Western Baltic, nauplii, to some extent, hatch and survive at this and even lower temperatures as shown by Javidpour et al (2010), who found barnacle nauplii in gut samples of Mnemiopsis leidyi in Kiel Fjord during most of winter. Surprisingly, though nauplii are obviously present in the water column at this time of the year, successful settlement is at an almost undetectable level between November and April (Wahl and Schütt, unpublished data;Thomsen et al 2010). Various reasons for settlement failure of barnacle larvae during winter have been documented as, e.g., food constraint (Barnes and Barnes 1958;Thiyagarajan et al 2002a), low temperature (Anil et al 1995), predation, starvation and misrouting (Crisp 1984), starvation in early naupliar stages (Lang and Marcy 1982), and Wnally the quality of released nauplii (Anil et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we know that in the Western Baltic, nauplii, to some extent, hatch and survive at this and even lower temperatures as shown by Javidpour et al (2010), who found barnacle nauplii in gut samples of Mnemiopsis leidyi in Kiel Fjord during most of winter. Surprisingly, though nauplii are obviously present in the water column at this time of the year, successful settlement is at an almost undetectable level between November and April (Wahl and Schütt, unpublished data;Thomsen et al 2010). Various reasons for settlement failure of barnacle larvae during winter have been documented as, e.g., food constraint (Barnes and Barnes 1958;Thiyagarajan et al 2002a), low temperature (Anil et al 1995), predation, starvation and misrouting (Crisp 1984), starvation in early naupliar stages (Lang and Marcy 1982), and Wnally the quality of released nauplii (Anil et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…If the barnacle population we investigated was optimally adapted to the local conditions, we would have expected best performance (e.g., survival) among those individuals that experienced conditions prevailing during peak settlement in July and August (Thomsen et al 2010), i.e., at about 20°C and 15 psu. However, larval duration was shortest at 28°C (regardless of salinity), metamorphosis success and overall survival (from start to end of Experiment I) was best at 5 psu (regardless of temperature).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ocean warming, "OW") and in carbonate chemistry and pH driven by increasing CO 2 emissions (i.e. ocean acidification, "OA") (IPCC 2014) are known to impact the integrity and morphology of the shell of adult marine organisms (Nienhuis et al, 2010;Thomsen et al, 2010;Melatunan et al, 2013). Some defence mechanisms such as decreased shell growth rates to preserve energy (Findlay et al, 2010) and increased calcification in a range of calcifying species across taxa have been observed in acidified conditions (Ries et al, 2009).…”
Section: Introductionmentioning
confidence: 99%